Attenuated Ca2+ release in a mouse model of limb girdle muscular dystrophy 2A. Issue 1 (December 2016) - DiFranco, Marino; Kramerova, Irina; Vergara, Julio; Spencer, Melissa
Abstract Background Mutations inCAPN3 cause limb girdle muscular dystrophy type 2A (LGMD2A), a progressive muscle wasting disease. CAPN3 is a non-lysosomal, Ca-dependent, muscle-specific proteinase. Ablation of CAPN3 (calpain-3 knockout (C3KO) mice) leads to reduced ryanodine receptor (RyR1) expression and abnormal Ca2+/calmodulin-dependent protein kinase II (Ca-CaMKII)-mediated signaling. We previously reported that Ca2+ release measured by fura2-FF imaging in response to single action potential stimulation was reduced in old C3KO mice; however, the use of field stimulation prevented investigation of the mechanisms underlying this impairment. Furthermore, our prior studies were conducted on older animals, whose muscles showed advanced muscular dystrophy, which prevented us from establishing whether impaired Ca2+ handling is an early feature of disease. In the current study, we sought to overcome these matters by studying single fibers isolated from young wild-type (WT) and C3KO mice using a low affinity calcium dye and high intracellular ethylene glycol-bis(2-aminoethylether)-n, n, n ′, n ′-tetraacetic acid (EGTA) to measure Ca2+ fluxes. Muscles were subjected to both current and voltage clamp conditions. Methods Standard and confocal fluorescence microscopy was used to study Ca2+ release in single fibers enzymatically isolated from hind limb muscles of wild-type and C3KO mice. Two microelectrode amplifier and experiments were performed under current or voltage clamp conditions. Calcium concentration changes were detected with an impermeant low affinity dye in the presence of high EGTA intracellular concentrations, and fluxes were calculated with a single compartment model. Standard Western blotting analysis was used to measure the concentration of RyR1 and theα subunit of the dihydropyridine (αDHPR) receptors. Data are presented as mean ± SEM and compared with the Student's test with significance set atp  < 0.05. Results We found that the peak value of Ca2+ fluxes elicited by single action potentials was significantly reduced by 15–20 % in C3KO fibers, but the kinetics was unaltered. Ca2+ release elicited by tetanic stimulation was also impaired in C3KO fibers. Confocal studies confirmed that Ca2+ release was similarly reduced in all triads of C3KO mice. Voltage clamp experiments revealed a normal voltage dependence of Ca2+ release in C3KO mice but reduced peak Ca2+ fluxes as with action potential stimulation. These findings concur with biochemical observations of reduced RyR1 and αDHPR levels in C3KO muscles and reduced mechanical output. Confocal studies revealed a similar decrease in Ca2+ release at all triads consistent with a homogenous reduction of functional voltage activated Ca2+ release sites. Conclusions Overall, these results suggest that decreased Ca2+ release is an early defect in calpainopathy and may contribute to the observed reduction of CaMKII activation in C3KO mice.